Investigation of total ionizing dose effects in 4H–SiC power MOSFET under gamma ray radiation. (August 2022) - Sun, Yabin; Wan, Xin; Liu, Ziyu; Jin, Hu; Yan, Junzheng; Li, Xiaojin; Shi, Yanling
Abstract: In this work, the gamma ray radiation-induced total ionizing dose (TID) effects in SiC power MOSFETs are investigated. The transistor characteristics, such as transfer curve, output curve, drain-source ON-state resistance and terminal capacitance, are characterized to quantify the radiation tolerance. The threshold voltage is found to be sensitive to radiation and decreases with radiation dose increasing. An increased drive current and decreased drain-source ON-state resistance are resulted due to the decreased threshold voltage. The increased gate input capacitance exists after radiation. Verified in Sentaurus TCAD 2D simulation, the radiation-induced trap charge and interface states at SiO2/SiC interface are found to dominate the degradation of electrical behaviors in SiC power MOSFET. Highlights: The total ionizing dose effects are investigated in SiC power MOSFETs. Vth is sensitive to radiation and decreases with dose increasing. Increased drive current and decreased drain-source ON-state resistance are resulted. The increased gate input capacitance exists after radiation. The underlying mechanism is verified with Sentaurus TCAD simulation.